Investigative evaluation of Cassia absus for antibacterial capacity and biomimetic synthesis of silver nanoparticles. Issue 8 (4th September 2018) - Jehan, Mehreen; Saeed, Fiza; Khan, Zanib; Shah, Muddassar; Sikandar, Ayesha; Inayat, Afia; Ali, Sartaj; Mehmood Khan, Arshad; Talib, Ayesha; Aasim, Muhammad; Ali Khan, Abid
Abstract : Cassia absus is used for medicinal purposes for a long time all over the world. In this study, the authors report the antimicrobial potential of C. absus extracts obtained with different solvents. The extract(s) obtained with ethyl acetate yielded the best antibacterial effects because of a rich supply of oxalates and alkaloids in it. The same extract was also exploited for reducing Ag + ions (to metallic Ag 0 ) for the synthesis of nanoparticles. Electron microscopy revealed that the silver nanoparticles were ∼18–25 nm in diameter. The Fourier‐transform infrared evaluation pointed towards the fact that flavonoids present in the plant extract were acting as reductants while amino groups were the bound stabilisation agents to the synthesised nanoparticles limiting the diameter to a certain threshold and avoiding aggregation naturally. A comparative antibacterial assay of C. absus versus Ag nanoparticles showed that the nanoparticles as well as organic (ethyl acetate) extract of the plant checked the growth of selected (MDR) superbugs. However, the biosynthesised Ag nanoparticles returned better antibacterial efficacies than ethyl acetate extract.